Evidence-Based Veterinary Medicine: A Tool for Evaluating the Healing Process After Surgical Treatment for Cranial Cruciate Ligament Rupture in Dogs - Pinna, Stefania; Lambertini, Carlotta; Grassato, Lisa; Romagnoli, Noemi (Frontiers in Veterinary Science, 2019)
This study aims to validate a tool, the Bologna healing stifle injury index (BHSII), for the evaluation of the clinical picture and the healing after surgical treatment for cranial cruciate ligament (CCL) rupture. The study included 158 client-owned dogs with CCL rupture and 20 healthy dogs. The BHSII was composed of a part for the clinician implemented by a part for the owner, with a total of 34 multiple-choice items. It was applied twice in the healthy dogs in order to test and retest the device. It was evaluated for reliability, validity and responsiveness to clinical changes involving the dogs treated at the time of surgery, and after 1, 3 and 6 months. Statistical analyses were performed and the intraclass correlation coefficient test was  0.9 and the Cronbach- was 0.84 suggesting good stability and good internal consistency of the tool. The area under the curve of the receiver operating characteristic curve was > 0.9, indicative of the high accuracy of this tool. The clinician survey correlated with the owner questionnaire. In dogs with CCL rupture, the scores of the BHSII increased significantly post-operatively as compared with baseline. In conclusion, this clinical study proved the reliability, validity and responsiveness of the BHSII. The results achieved from the BHSII provided an instantaneous, collective complete vision of the healing process of the stifle joints treated. It can be considered a valid tool for collecting data and for assessing successful surgical treatment in clinical practice.